Preliminary indications of the burden of COVID-19 among people who inject drugs in England and Northern Ireland and the impact on access to health and harm reduction services. (March 2021) - Croxford, S.; Emanuel, E.; Ibitoye, A.; Njoroge, J.; Edmundson, C.; Bardsley, M.; Heinsbroek, E.; Hope, V.; Phipps, E.
Abstract: Objective: The aim of the study was to describe the impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic on people who inject drugs (PWID) in England, Wales and Northern Ireland. Study design: This is a cross-sectional Unlinked Anonymous Monitoring (UAM) Survey of PWID. Methods: People who had ever injected psychoactive drugs were recruited to the UAM Survey by specialist drug/alcohol services in England, Wales and Northern Ireland. From June 2020, in addition to providing a dried blood spot sample and completing the UAM behavioural questionnaire, participants were asked to complete an enhanced coronavirus disease 2019 (COVID-19) questionnaire. Preliminary data are presented to the end of October and were compared with data from the 2019 UAM Survey, where possible. Results: Between June and October, 288 PWID were recruited from England and Northern Ireland. One in nine (11%; 29/260) PWID reported testing positive for SARS-CoV-2 or experiencing COVID-19 symptoms. Fifteen percent (26/169) reported injecting more frequently in 2020 than in 2019; cocaine injection in the preceding four weeks increased from 17% (242/1456) to 25% (33/130). One in five PWID (19%; 35/188) reported difficulties in accessing HIV and hepatitis testing, and one in four (26%; 47/179) reported difficulties in accessing equipment for safer injecting. Conclusions: Our preliminary findings suggest that PWID have experienced negative impacts on health, behaviours and access to essential harm reduction, testing and treatment services owing to the COVID-19 pandemic. Continued monitoring through surveillance and research is needed to understand the subsequent impact of COVID-19 on blood-borne virus transmission in this population and on health inequalities. Highlights: People who inject drugs (PWID) in England/Northern Ireland are at risk of coronavirus disease 2019. Patterns of psychoactive drug use have shifted over the course of the pandemic. Of particular concern, access to essential services for PWID has been restricted.